Influence of processing on the ethylene-vinyl alcohol (EVOH) properties: Application of the successive self-nucleation and annealing (SSA) technique (eXPRESS Polymer Letters)
Films of EVOH copolymers, processed three times by twin-screw extrusion were prepared using a cast-film line. The variation on the melt flow rate (MFR) and rheological behaviour of the films were determined, as well as the thermal properties assessed by differential scanning calorimetry (DSC) and dynamic-mechanical thermal analysis (DMTA). As the results showed that the reprocessing induced an increase in the viscosity and orientation of the films, it was suggested that structural modifications from chain-extension or cross-linking reactions promoted by hydroxyl and residual acetoxyl groups, could be occurring. The successive self-nucleation and annealing (SSA) technique was applied, evidencing the structural modifications on the EVOH copolymer.